Intraventricular Neurocysticercosis and Bruns Syndrome: A Case Report - Baskota, Narendra Prasad; Singh, K. (Journal of Nepalgunj Medical College, 2019)
Neurocysticercois is a common neurological infection but intraventricular NCC is rare even in endemic areas. Here we discuss a case of intraventricular NCC located at foramen of monro leading to Bruns syndrome.